2019
DOI: 10.1088/1742-6596/1387/1/012123
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Use Web-Based Learning Media for Information and Communication Technology in Senior High School

Abstract: The purposes of this study to develop an effective web-based learning media. Methodology of this research is a Research and Develompment (R & D). Development model used is Instructional Development Institute (IDI). The principle approach applied IDI system consists of determination, development, and evaluation. Research design used is descriptive quantitative. The instruments used is a questionnaire to measure validity, practicalities and posttest to measure effectiveness. Then data was analyzed using stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Dalam implementasinya pembelajararan e-learning menggunakan alat elektronik menggunakan format layanan audio, video, komputer atau kombinasi ketiganya. Sehingga, dapat diunggah di internet agar dapat menjadi sumber belajar matematika yang dapat dipelajari peserta didik secara online (Ahyanuardi & Ratih, 2019). Salah satu penyedia website video-sharing yang mengizinkan pengguna untuk berbagi video, menonton dan mengunggah video adalah Youtube (Suwarno, 2017).…”
Section: Pendahuluanunclassified
“…Dalam implementasinya pembelajararan e-learning menggunakan alat elektronik menggunakan format layanan audio, video, komputer atau kombinasi ketiganya. Sehingga, dapat diunggah di internet agar dapat menjadi sumber belajar matematika yang dapat dipelajari peserta didik secara online (Ahyanuardi & Ratih, 2019). Salah satu penyedia website video-sharing yang mengizinkan pengguna untuk berbagi video, menonton dan mengunggah video adalah Youtube (Suwarno, 2017).…”
Section: Pendahuluanunclassified
“…The results of the research show that the media is effective because it can improve students' ICT literacy [14]. Furthermore, other researchers have also developed web-based learning media, with results of their research showing that the media developed was effective for improving student learning outcomes [15]. Another researcher had developed a website-based learning media using Moodle, and the results showed that the media was able to increase student motivation in learning [16].…”
mentioning
confidence: 99%